Intraday markets for power: Discretizing the continuous trading? - Karsten Neuhoff; Nolan Ritter; Aymen Salah-Abou-El-Enien; Philippe Vassilopoulos (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
A fundamental question regarding the design of electricity markets is whether adding auctions to the continuous intraday trading is improving the performance of the market. To approach this question, we assess the experience with the implementation of the 3 pm local auction for quarters in Germany at the European Power Exchange (EPEX SPOT) in December 2014 to assess the impact on trading volumes/liquidity, prices, as well as market depth. We discuss further opportunities and challenges that are linked with a potential implementation of an intraday auction.
Keywords: C5; C57; C93; D44; D47; L50; 330; auctions; electricity; empirical analysis; market design